Ionic liquids for the inhibition of gas hydrates. A review - Ul Haq, I. (Springer Science and Business Media Deutschland GmbH, 2022)
The formation of gas hydrates is a major issue during the operation of oil and gas pipelines, because gas hydrates cause plugging, thereby disrupting the normal oil and gas flows. A solution is to inject gas hydrate inhibitors such as ionic liquids. Contrary to classical inhibitors, ionic liquids act both as thermodynamic inhibitors and hydrate inhibitors, and as anti-agglomerates. Imidazolium-based ionic liquids have been found efficient for the inhibition of CO2 and CH4 hydrates. For CO2 gas hydrates, N-ethyl-N-methylmorpholinium bromide showed an average depression temperature of 1.72Â K at 10Â wt concentration. The induction time of 1-ethyl-3-methyl imidazolium bromide is 36.3Â h for CO2 hydrates at 1Â wt concentration. For CH4 hydrates, 1-ethyl-3-methyl-imidazolium chloride showed average depression temperature of 4.80Â K at 40Â wt. For mixed gas hydrates of CO2 and CH4, only quaternary ammonium salts have been studied. Tetramethyl ammonium hydroxide shifted the hydrate liquid vapour equilibrium to 1.56Â K at 10Â wt, while tetrabutylammonium hydroxide showed an induction time of 0.74Â h at 1Â wt concentration. Â© 2022, The Author(s), under exclusive licence to Springer Nature Switzerland AG.